"Law, liberty and livelihood" - "Shah, Partha J. (ed.)" (New Delhi, 2005)
It documents through primary research the (3z(Bofficial(3y (Bas well as the (3z(Bactual(3y (Bregulatory and licensing processes by direct interactions with varied stakeholders$1 (Brailway porters, street vendors, small shop keepers, cycle and auto rickshaw drivers, household-based industries, as well as small school operators.s
Keywords: Urbanisation